HCMV pUL135 remodels the actin cytoskeleton to impair immune recognition of infected cells - Stanton, Richard J; Prod'homme, Virginie; Purbhoo, Marco A; Moore, Melanie; Aicheler, Rebecca J; Heinzmann, Marcus; Bailer, Susanne M; Haas, Jürgen; Antrobus, Robin; Weekes, Michael P; Lehner, Paul J; Vojtesek, Borivoj; et al. (Cell host & microbe, 2014)
Immune evasion genes help human cytomegalovirus (HCMV) establish lifelong persistence. Without immune pressure, laboratory-adapted HCMV strains have undergone genetic alterations. Among these, the deletion of the UL/b' domain is associated with loss of virulence. In a screen of UL/b', we identified pUL135 as a protein responsible for the characteristic cytopathic effect of clinical HCMV strains that also protected from natural killer (NK) and T cell attack. pUL135 interacted directly with abl interactor 1 (ABI1) and ABI2 to recruit the WAVE2 regulatory complex to the plasma membrane, remodel the actin cytoskeleton and dramatically reduce the efficiency of immune synapse (IS) formation. An intimate association between F-actin filaments in target cells and the IS was dispelled by pUL135 expression. Thus, F-actin in target cells plays a critical role in synaptogenesis, and this can be exploited by pathogens to protect against cytotoxic immune effector cells. An independent interaction between pUL135 and talin disrupted cell contacts with the extracellular matrix.
Keywords: rodina proteinů Wiskottova-Aldrichova syndromu; mikrofilamenta; Adaptor Proteins, Signal Transducing; Viral Proteins; adaptorové proteiny signální transdukční; buňky NK; cytoskeletální proteiny; lidé; Talin; Wiskott-Aldrich Syndrome Protein Family; CD8-Positive T-Lymphocytes; Immunomodulation; Immunological Synapses; Cytomegalovirus; Cytoskeletal Proteins; CD8-pozitivní T-lymfocyty; Killer Cells, Natural; imunologické synapse; virové proteiny; interakce hostitele a patogenu; talin; Host-Pathogen Interactions; imunomodulace; Actin Cytoskeleton; Humans